(untitled) (Scientia Agricola, 2007)
The Araucaria Forest is a sub-type of the Atlantic Forest, dominated by Araucaria angustifolia, which is considered an endangered species. The understory has a high diversity of plant species, including several legumes. Many leguminous plants nodulate with rhizobia and fix atmospheric nitrogen, contributing to forest sustainability. This work aimed at bacteria isolation and phenotypic characterization from the root nodules of legumes occurring in Araucaria Forests, at Campos do Jordão State Park, Brazil. Nodule bacteria were isolated in YMA growth media and the obtained colonies were classified according to their growth characteristics (growth rate, color, extra cellular polysaccharide production and pH change of the medium). Data were analyzed by cluster and principal components analysis (PCA). From a total of eleven collected legume species, nine presented nodules, and this is the first report on nodulation of five of these legume species. Two hundred and twelve bacterial strains were isolated from the nodules, whose nodule shapes varied widely and there was a great phenotypic richness among isolates. This richness was found among legume species, individuals of the same species, different nodule shapes and even among isolates of the same nodule. These isolates could be classified into several groups, two up to six according to each legume, most of them different from the used growth standards Rhizobium tropici, Bradyrhizobium elkanii and Burkholderia sp. There is some evidence that these distinct groups may be related to the presence of Burkholderia spp. in the nodules of these legumes.